Incorporation of brentuximab vedotin into first-line treatment of advanced classical Hodgkin's lymphoma: final analysis of a phase 2 randomised trial by the German Hodgkin Study Group. Issue 12 (December 2017) - Eichenauer, Dennis A; Plütschow, Annette; Kreissl, Stefanie; Sökler, Martin; Hellmuth, Johannes C; Meissner, Julia; Mathas, Stephan; Topp, Max S; Behringer, Karolin; Klapper, Wolfram; Kuhnert, Georg; Dietlein, Markus; et al.
Summary: Background: A high proportion of patients with relapsed classical Hodgkin's lymphoma achieve a response with the antibody-drug conjugate brentuximab vedotin, and the drug is well tolerated. We modified the escalated BEACOPP regimen (eBEACOPP; bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone) and implemented brentuximab vedotin with the aim to reduce toxic effects while maintaining the protocol's efficacy. Methods: We did an open-label, multicentre, randomised phase 2 study at 20 study sites in Germany. Adult patients (aged 18–60 years) with newly diagnosed, advanced, classical Hodgkin's lymphoma were randomly assigned (1:1) to treatment with six cycles of either BrECAPP (brentuximab vedotin 1·8 mg/kg on day 1, etoposide 200 mg/m 2 on days 2–4, doxorubicin 35 mg/m 2 on day 2, cyclophosphamide 1250 mg/m 2 on day 2, procarbazine 100 mg/m 2 on days 2–8, and prednisone 40 mg/m 2 on days 2–15) or BrECADD (brentuximab vedotin 1·8 mg/kg on day 1, etoposide 150 mg/m 2 on days 2–4, doxorubicin 40 mg/m 2 on day 2, cyclophosphamide 1250 mg/m 2 on day 2, dacarbazine 250 mg/m 2 on days 3–4, and dexamethasone 40 mg on days 2–5). Randomisation was done centrally by stratified minimisation, with study site and sex as stratification factors. The co-primary endpoints were complete response to chemotherapy and complete remission at the end of treatment, which were assessed by intention to treat. Patients who were found not to meet inclusion criteria after randomisation or without restaging data after two cycles of study treatment were excluded from the primary endpoint analysis. All patients who started study treatment were assessable for safety. This report presents the final analysis at a median follow-up of 17 months (IQR 13·2–21·5). The preplanned 2-year follow-up analysis is yet to be reported. This trial is registered withClinicalTrials.gov, numberNCT01569204 . Findings: Between Oct 26, 2012, and May 15, 2014, 104 patients were enrolled to the study (52 were assigned to each study arm). Two patients dropped out before the start of study treatment because of acute infection (n=1) and withdrawal of consent (n=1) and one patient was excluded because of intermediate-stage disease (all were assigned BrECAPP). 42 (86%, 95% CI 73–94) of 49 patients assigned BrECAPP achieved a complete response after chemotherapy and 46 (94%, 95% CI 83–99) had complete remission as their final treatment outcome. In the BrECADD group, 46 (88%, 95% CI 77–96) of 52 patients achieved both a complete response after chemotherapy and complete remission as their final treatment outcome. 58 serious adverse events were reported, 32 events in 21 of 50 patients who received BrECAPP and 26 events in 18 of 52 patients who received BrECADD. The most common grade 3–4 toxic effects were haematological adverse events (91 [89%] of 102 patients). Grade 3–4 organ toxic effects were reported in seven (17%) of 42 patients assigned BrECAPP and two (4%) of 46 allocated BrECADD. 16 (32%) of 50 patients assigned BrECAPP and 18 (35%) of 52 allocated BrECADD had grade 1–2 peripheral neuropathy, and one (2%) patient assigned BrECAPP developed grade 3 peripheral neuropathy; all but one case (allocated BrECAPP) resolved. No deaths were reported during the follow-up period. Interpretation: Both eBEACOPP variants met the co-primary efficacy endpoints. Particularly, the BrECADD regimen was associated with a more favourable toxicity profile and was, therefore, selected to challenge standard eBEACOPP for the treatment of advanced classical Hodgkin's lymphoma in the phase 3 HD21 study by the German Hodgkin Study Group (NCT02661503 ), which aims to further reduce treatment-related morbidity. Funding: Takeda Pharmaceuticals.